Assessing the Test-Retest repeatability of the Vietnamese Version of the Natioal Eye Institute 25-Item Visual Function Questionnaire Among Bilateral Cataract Patients For a Vietnamese Population - To, K.; Meuleners, Lynn; Chen, Huei-Yang; Lee, Andy; Do, D.; Duong, D.; Phi, T.D.; Tran, H.H.; Nguyen, N.D. (Wiley-Blackwell Publishing Asia, 2014)
Aim: To determine the test–retest repeatability of the National Eye Institute 25-item Visual Function Questionnaire (NEI VFQ-25) for use with older Vietnamese adults with bilateral cataract. Methods: The questionnaire was translated into Vietnamese and back-translated into English by two independent translators. Patients with bilateral cataract aged 50 and older completed the questionnaire on two separate occasions, one to two weeks after first administration of the questionnaire. Test–retest repeatability was assessed using the Cronbach's α and intraclass correlation coefficients. Results: The average age of participants was 67 ± 8 years and most participants were female (73%). Internal consistency was acceptable with the α coefficient above 0.7 for all subscales and intraclass correlation coefficients were 0.6 or greater in all subscales. Conclusion: The Vietnamese NEI VFQ-25 is reliable for use in studies assessing vision-related quality of life in older adults with bilateral cataract in Vietnam. We propose some modifications to the NEI-VFQ questions to reflect activities of older people in Vietnam.